PERAN MANAJEMEN KOMPENSASI DALAM MENINGKATKAN KINERJA PENGAJAR DAN PEMBELAJARAN - Kumala, Sania; Sukarman, Sukarman; Hartini, Rigen; Agustin, Fariqoh (STKIP Pesisir Selatan, 2025)
Education is a vital aspect in improving the quality of human resources in a country. The performance of teaching and learning is greatly influenced by the motivation and well-being of educators. Compensation management, which includes salary, benefits, and non-financial rewards, plays an important role in enhancing teaching quality. This article aims to examine the role of compensation management in improving teaching and learning performance. The research uses a literature review method by analyzing previous studies on the influence of compensation on teacher motivation and performance. The results of the research indicate that a fair and transparent compensation system can enhance job satisfaction, motivation, and teacher productivity. However, there are challenges in implementing compensation, such as salary disparities, budget limitations, and a lack of non-financial rewards. This study suggests that educational institutions should improve fairness in compensation distribution, consider non-financial rewards, and align compensation with teacher performance to achieve significant improvements in education quality.